2013
DOI: 10.4067/s0717-97072013000400027
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins of Haplopappus Multifolius and Derivative as Inhibitors of Lox: Evaluation in-Vitro and Docking Studies

Abstract: Several natural compounds containing a coumarin moiety have been reported. They have multiple biological activities, e.g., as scavengers of reactive oxygen species (ROS) and to reduce the inflammatory processes by inhibition of enzymes like COX or LOX.A study was made of the inhibitory capacity of seven natural coumarins and one derivative of esculetin, against soybean 15-lipoxygenase (15-sLOX). The studied coumarins showed interesting degrees of inhibition compared to quercetin, a known LOX inhibitor. Docking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…3) is a kind of coumarin derivative, with an inhibition of 34.75% at a concentration of 12.7 μM against 15-LOX. 42 In molecular docking study, its bond energy at the bonding site with 15-LOX and 5-LOX was −0.19 and 3.11 kcal mol −1 , respectively, which indicated that this compound has more affinity for human 5-LOX than 15-LOX. This phenomenon could result from the size of the catalytic cavity of 5-LOX being bigger than that of 15-LOX.…”
Section: Inhibitors Obtained By the Modification Of Previously Known mentioning
confidence: 94%
“…3) is a kind of coumarin derivative, with an inhibition of 34.75% at a concentration of 12.7 μM against 15-LOX. 42 In molecular docking study, its bond energy at the bonding site with 15-LOX and 5-LOX was −0.19 and 3.11 kcal mol −1 , respectively, which indicated that this compound has more affinity for human 5-LOX than 15-LOX. This phenomenon could result from the size of the catalytic cavity of 5-LOX being bigger than that of 15-LOX.…”
Section: Inhibitors Obtained By the Modification Of Previously Known mentioning
confidence: 94%
“…In addition, lipoxygenases are a family of non-heme iron-containing enzymes and are involved in the synthesis of inflammatory cytokines such as leukotrienes. A previous study demonstrated that the inhibition rate of esculetin on soybean 15-lipoxygenase at a concentration of 28.1 µM is 40.50% (78). Esculetin can also inhibit the activity of 5-lipoxygenase with an IC50 value of 6.6 µM (79).…”
Section: Anti-inflammatory Activities Of Esculetin and Esculinmentioning
confidence: 97%
“…To the best of our knowledge, there are no crystal structures containing cocrystallized structures of compounds investigated in this study with soybean lipoxygenase. Therefore, molecular docking was performed on soybean lipoxygenase-Ib (PDB ID: 5T5V) (SRIVASTAVA et al, 2016;TORRES et al, 2013). Initially, the protein was prepared for molecular modelling after being loaded into the UCSF Chimera v1.10.1 software (PETTERSEN et al, 2004) for Linux 64 bit architecture and visually inspected.…”
Section: The Structure Crystal Preparation Soybean Lipoxygenasementioning
confidence: 99%